The Impact of The Kaizen Methodology for Continuous Improvement on Job Performance: An Applied Study on The Employees of Imperial Knight Holding Company, Sulaymaniyah Governorate - Falah Hassan Ahmed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The research dealt with the concept of the Kaizen methodology for continuous improvement and job performance, This research aimed to identify the extent of the impact of the Kaizen methodology for continuous improvement on job performance, by addressing the main problematic about knowing the impact of the Kaizen methodology for continuous improvement on job performance, the descriptive approach was adopted in the aspect Theoretical As for the practical side, a questionnaire was relied on to collect the initial data which has been distributed it to the research sample, which was represented by all employees of the Imperial Knight Company, the number of valid and approved forms reached (41), and in sight of this, data were collected and analyzed, and the research hypothesis was tested. The statistical program (SPSS) version (24) has been used for purpose of analysis of data, and the research reached a number of results, the most important of which was that there is a statistically significant effect of the Kaizen methodology for continuous improvement on job performance. and one of the most important recommendations made by the research is the need to provide a good communication system to contribute to the continued participation of workers in the continuous improvement processes effectively.